Development of heavyweight concrete incorporating steel slag as aggregate for potential application of wave-dissipating blocks in Vietnam - Duong, Trung Quoc; Tran, Thanh Nhan; Tran, Thi Ngoc Quynh; Nguyen, Thi Le Huyen; Do, Quang Thien (Hue University Journal of Science: Natural Science, 2026)
In 2024, Vietnam ranked as the 11th largest steel producer worldwide, with an annual crude steel output of approximately 22 million tonnes, generating a substantial amount of steel slag (SS). As most major steel plants in Vietnam employ Basic Oxygen Furnace (BOF) technology, BOF slag represents the dominant type of SS produced. This study proposes and evaluates the use of mixed BOF and cast SS, based on actual production proportions at the Formosa steel plant, as coarse aggregates for heavyweight concrete (SS concretes) under Vietnamese conditions. Four qualified SS types were combined and applied in concrete mixtures across three grading scenarios. The results show that SS concretes exhibit more consistent compressive strength development and more significant strain at failure than conventional concretes made with natural aggregates. The 28-day compressive strength of the SS concretes reached 113.6–117.8% of the target strength for M400 concrete. Owing to the higher density of the SS aggregates (1.23–1.42 times that of natural aggregates), the resulting concretes achieved densities 1.13–1.16 times greater than conventional mixes, with average values ranging from 2.64 to 2.73 t/m³, meeting the requirements for heavyweight concrete. These findings indicate that SS concrete has potential for applications such as wave-dissipating blocks; however, further hydraulic investigations are required to confirm this performance.